Measuring food security in the Republic of Serbia - Papić-Brankov Tatjana; Milovanović Miloš (Ekonomika Poljoprivrede (1979), 2015)
The overall goal of this paper is analysis of Serbian food security system across a set of indicators, with special emphasis to 2012 Global Food Security Index (GFSI). The results generally provided two major weakness of the Serbian food system: Gross domestic product (GDP) per capita based on purchasing power parity and Corruption. Paper points out the need to improve the current food security system and proposed a number of measures for its improvement. Among other things appropriate nutritional standards and strategies will have to be adopted; investors' confidence must be strengthened and must be dealt with in a serious fight against corruption in the agriculture and food sector. The development of rural areas, reducing regional disparities and stabilization of agricultural production will certainly contribute to the tough battle against poverty.